Impact of an exergame intervention on cognitive-motor functions and training experience in young team sports athletes: a non-randomized controlled trial - Martin-Niedecken, Anna Lisa; Bucher, Valentin; Adcock, Manuela; de Bruin, Eling D.; Schättin, Alexandra (Frontiers in Sports and Active Living, 2023)
Team sports athletes need excellent perceptual-cognitive skills, particularly executive functions (EF) to strategically perform on the field. The transfer effect of cognitive training might be accomplished by the inclusion of cognitive stimuli into a physically active environment as these couplings are required in real game situations. A training approach that combines both components is exergaming. The primary objective of this study was to gain preliminary insights into the effects of exergaming on cognitive-motor functions in young game sport athletes. The secondary objective was to investigate participants' training experience and well-being over time. Participants were assigned to the intervention or control group. In the intervention group, participants trained with the ExerCube – a mixed reality exergame. The training was planned for 10 weeks (two sessions per week à 25 minutes) but had to be shortened by two weeks due to COVID-19 restrictions. The control group had no additional training. Outcomes included a computer-based alertness test and a cognitive-motor test battery to assess different EF (flexibility, divided attention, and inhibition) via a specific FitLight setup. Twenty-four athletes (mean age (± SD) 15.0 ± 0.7 years) participated either in the intervention group (N=12; male N=6; female N=6; 14.7 ± 0.5 years) or the control group (N=12; male N=7; female N=5; 15.3 ± 0.8 years). Participants in the intervention group performed on average 9.4 ± 3.3 training sessions over eight weeks. Significant time x group interactions were evident for the cognitive-motor This is a provisional file, not the final typeset article sub-tests flexibility (F=12.176, p<0.001, d=1.488) and divided attention for auditive stimuli (F=9.776, p=0.002, d=1.404) in favour of the intervention group. For the alertness test, a medium effect size (time x group interaction) was seen for the variability of the reaction time (F=2.196, p=0.138, d=0.632) in favour of the intervention group. Training experience and well-being were consistently at medium to high levels. The ExerCube training yielded positive effects on concentration, flexibility, and divided attention indicating that exergaming can be an innovative training approach for team sports athletes.